Performance and sustainability in hybrid concrete: A study of recycled aggregates and activated fly ash - Salman Masood; Lu Dagang; Kennedy C. Onyelowe; Mudassar Munir Shah; Hamad Almujibah; Aïssa Rezzoug; Hawreen Ahmed; Tabinda Ramzan; Nabil Ben Kahla; Nejib Ghazouani (Ain Shams Engineering Journal, 2025)
Construction and demolition waste (CDW), particularly concrete debris, poses significant environmental challenges globally. This study investigates the sustainable use of recycled coarse aggregates (RCA) combined with activated fly ash (AFA) in hybrid concrete mixtures to mitigate environmental impacts while maintaining performance. Laboratory tests evaluated mechanical properties, durability, and environmental footprints of concrete mixes with varying RCA replacement ratios (0%–100%) and fly ash activation using a sodium hydroxide/sodium silicate solution. Results indicate that RCA replacement up to 60% leads to a reduction in compressive strength when used alone; however, incorporating 25% activated fly ash effectively recovers much of this strength loss, achieving near-comparable performance to conventional concrete. Durability assessments reveal enhanced resistance to chemical attack and chloride ion penetration in mixes containing activated fly ash. Environmental impact analysis demonstrates substantial reductions in carbon emissions (43%), aquatic acidification (30%), and non-renewable energy use (29%) with the hybrid RCA-AFA concrete. Multi-criteria TOPSIS analysis confirms the superiority of activated fly ash mixes in balancing mechanical performance and sustainability. These findings highlight the potential of combining RCA with chemically activated fly ash to develop durable, high-performance concrete that supports circular economy goals and sustainable construction practices.